2006
DOI: 10.1159/000097516
|View full text |Cite
|
Sign up to set email alerts
|

Activating of ATP-Dependent K<sup>+</sup> Channels Comprised of K<sub>ir</sub> 6.2 and SUR 2B by PGE<sub>2</sub> Through EP<sub>2</sub> Receptor in Cultured Interstitial Cells of Cajal from Murine Small Intestine

Abstract: The interstitial cells of Cajal (ICC) are pacemaker cells in gastrointestinal tract and generate an electrical rhythm in gastrointestinal muscles. We investigated the possibility that PGE2 might affect the electrical properties of cultured ICC by activating ATPdependent K+ channels and, the EP receptor subtypes and the subunits of ATP-dependent K+ channels involved in these activities were identified. In addition, the regulation of intracellular Ca2+ ([Ca2+ Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…In our previous study, we showed prostaglandin E2 and F2α have actions on pacemaker activity in ICC [24,29]. Whether or not the effect of 5-HT on ICC is by COX induction was not proven in the current study, thus further studies are needed.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In our previous study, we showed prostaglandin E2 and F2α have actions on pacemaker activity in ICC [24,29]. Whether or not the effect of 5-HT on ICC is by COX induction was not proven in the current study, thus further studies are needed.…”
Section: Discussionmentioning
confidence: 64%
“…It is well-known that inositol 1,4,5-triphosphate receptor plays an important role for generating spontaneous electrical activity in pacemaker cells [22] ]i oscillations in ICC from mouse ileum [23], and these actions in ICC are considered to be the primary pacemaker activity in the gut. Furthermore in our previous reports, we showed spontaneous [Ca 2+ ]i oscillations in ICC and found that carbachol and PGE2 regulated the [Ca 2+ ]i oscillations [24,25], suggesting that [Ca 2+ ]i in ICC is the important element regulating pacemaker activity. In the studies conducted on 5-HT, the intracellular calcium was increased and returned back to normal conditions showing a similar effect as electrophysiologic studies.…”
Section: Discussionmentioning
confidence: 67%
“…Activation of ATP-sensitive K + channels produces hyperpolarization of the cell membrane [11]. Previously, we reported that ATP-sensitive K + channels existed in mouse intestinal ICC [12]. Related to this, there are some reports that the activation of ATP-sensitive channels by NaHS was proposed as the consequence of ATP depletion due to the inhibition by sulfide of the oxidative phosphorylation [10], with partial involvement of ATP-sensitive K + channels on NaHS-induced contraction and relaxation in rat and mouse aorta [13].…”
Section: Discussionmentioning
confidence: 98%
“…Activation of ATP-sensitive K + channels produces hyperpolarization of cell membrane, thus decreasing Ca 2+ influx and inhibiting cell excitability (Rodrigo and Standen, 2005). We also reported that ATP-sensitive K + channels exist in murine intestinal ICC (Choi et al, 2006). Furthermore EGCG has been reported to inhibit ATP-sensitive K + channel which is widely distributed in human tissues, and also all subtypes of ATP-sensitive K + channel (Baek et al, 2005).…”
Section: Discussionmentioning
confidence: 66%